2008
DOI: 10.1002/kin.20293
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of myristic acid and isopropyl alcohol esterification reaction with homogeneous and heterogeneous catalysts

Abstract: The reaction of myristic acid (MA) and isopropyl alcohol (IPA) was carried out by using both homogeneous and heterogeneous catalysts. For a homogeneously catalyzed system, the experimental data have been interpreted with a second order, using the power-law kinetic model, and a good agreement between the experimental data and the model has been obtained. In this approach, it was assumed that a protonated carboxylic acid is a possible reaction intermediate. After a mathematical model was proposed, reaction rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…A second order reversible PH model was demonstrated to fit the experimental data and this model gave a satisfactory interpretation of the experimental data. A similar finding was reported by Reference [12] when they investigated the esterification of myristic acid using homogeneous (p-toulene sulfonic acid) and heterogeneous (Amberlyst 15 and Degussa) catalysts. Their experimental data have been interpreted with a second order kinetic model and a good agreement was achieved between the experimental data and the model.…”
Section: Introductionsupporting
confidence: 87%
“…A second order reversible PH model was demonstrated to fit the experimental data and this model gave a satisfactory interpretation of the experimental data. A similar finding was reported by Reference [12] when they investigated the esterification of myristic acid using homogeneous (p-toulene sulfonic acid) and heterogeneous (Amberlyst 15 and Degussa) catalysts. Their experimental data have been interpreted with a second order kinetic model and a good agreement was achieved between the experimental data and the model.…”
Section: Introductionsupporting
confidence: 87%
“…This (the separation of water in a second phase) has already been reported in the case of the esterification of myristic acid [28].…”
Section: Kinetic Modelmentioning
confidence: 76%
“…Although to our knowledge DBSA has not been used so far in this type of reaction, the esterification of many carboxylic acids has already been addressed by different authors and hence the variables that influence the kinetics and equilibrium of the reaction are well known: temperature (T), the catalyst/fatty acid molar ratio (Cat), the methanol/fatty acid molar ratio (Met), the initial water/fatty acid weight ratio (H 2 O) and the stirring rate [26][27][28][29]. Accordingly, in this work we studied the influence of all these variables and, additionally, the influence of the presence of triglycerides in the reaction mixture.…”
Section: Experimental Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Aafaqi et al [8] reported that the homogeneous catalyst gives better conversion than the heterogeneous catalyst for esterification of palmitic acid with isopropanol. Yalcinyuva et al [9] reported similar comparative results for esterification of myristic acid with isopropyl alcohol. They concluded that heterogeneous catalysts gave poor conversions due to the diffusion problem of fatty acid into the pores of the catalyst.…”
Section: Introductionmentioning
confidence: 75%